2008
DOI: 10.1055/s-0028-1103513
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal Translucency Thickness in Euploid Fetuses: Is Two Millimeters Too Risky?

Abstract: We sought to determine whether nuchal translucency (NT) thickness of >or= 2 mm poses a risk for adverse perinatal outcome. A prospective observational study was conducted including all singleton pregnancies undergoing NT screening between 11 and 13.6 weeks' gestation, from January 1999 to October 2006, in a University Medical Center. Aneuploid and malformed fetuses were excluded from the analysis, as well as fetuses from pregnancies that ended before 22 gestational weeks. A comparison was performed between fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…normal fetuses posed a significant risk for adverse perinatal outcome. 21 A study conducted by Suoka et al also reported higher risk of adverse outcome when the fetus had persistent second trimester nuchal fold. These fetuses are also likely to develop hydrops and die in utero, 22 and the risk increases exponentially according to the nuchal translucency thickness.…”
Section: Resultsmentioning
confidence: 96%
“…normal fetuses posed a significant risk for adverse perinatal outcome. 21 A study conducted by Suoka et al also reported higher risk of adverse outcome when the fetus had persistent second trimester nuchal fold. These fetuses are also likely to develop hydrops and die in utero, 22 and the risk increases exponentially according to the nuchal translucency thickness.…”
Section: Resultsmentioning
confidence: 96%
“…Of these, 214 were excluded, the primary reason being the inclusion of both miscarriages and stillbirths or neonatal deaths and stillbirths in the mortality outcome measure or stillbirth in a composite outcome measure (21%), which did not allow the predictive accuracy of tests for stillbirths alone to be calculated. Seventy‐one studies (50 cohort and 21 case–control studies), assessing a total of 16 single and five combined tests, met the inclusion criteria (see Figure S1). Box 1 lists the first‐trimester and second‐trimester tests to predict stillbirth in unselected pregnant women that were identified in the review.…”
Section: Resultsmentioning
confidence: 99%
“…A large cohort study reported an antepartum stillbirth prevalence of 3.5 per 1000 births . Thirty‐four studies provided predictive accuracy data on five fetoplacental peptides (18 on alphafetoprotein [ α ‐FP], 15 on human chorionic gonadotrophin [hCG], three on unconjugated estriol [uE 3 ], seven on pregnancy‐associated plasma protein A [PAPP‐A], and one on inhibin A); 19 on six ultrasound imaging‐related tests (seven on uterine artery Doppler velocimetry, four each on nuchal translucency and suboptimal fetal growth, two on echogenic bowel, and one each on short femur and ductus venosus); 12 on five combinations of tests (three on first‐trimester screening for Down syndrome, five on second‐trimester screening for Down syndrome, one on first‐ and second‐trimester sequential integrated screening for Down syndrome and three on multivariable prediction models,); four on thyroid function‐related tests; two each on maternal haemoglobin levels and 25‐hydroxyvitamin D serum levels; and one on cervicovaginal infection . Few studies reported estimates of the predictive accuracy for stillbirths according to the timing of death, gestational age at birth, presumed cause of death or associated medical/obstetric disorder .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Fink et al . indicated that fetal NT thickness of 2 mm or more posed a significant risk for adverse perinatal outcome (adjusted OR 14.3; 95% CI 1.8–35; P < 0.001) 39 . This showed that the fetal NT cut‐off point can vary greatly from 2 to 10 mm, depending on the chromosomal defect to be detected; with rates varying from 11 to 88% 2 …”
Section: Discussionmentioning
confidence: 98%
“…14 With cut-off point of 2.4 mm, we also found that the rate of trisomy 21 was three times higher than trisomy 18 (12/16 cases of trisomy 21 vs 4/7 cases of trisomy 18) as reported by Acacio et al 14 Recently, Fink et al indicated that fetal NT thickness of 2 mm or more posed a significant risk for adverse perinatal outcome (adjusted OR 14.3; 95% CI 1.8-35; P < 0.001). 39 This showed that the fetal NT cut-off point can vary greatly from 2 to 10 mm, depending on the chromosomal defect to be detected; with rates varying from 11 to 88%. 2 We conclude that an increased fetal NT of 2.4 mm corresponded to a suitable cut-off point for use in the existing screening program for detection of fetal abnormalities (especially trisomy 21) in the south of Vietnam.…”
Section: Discussionmentioning
confidence: 99%